Male μαστoι in Revelation 1.13 - Rainbow, Jesse (2007)
This essay explains the strange occurrence of `male breasts' in the vision of the Son of Man (Rev. 1.13) by appealing to an anomaly in the LXX Song of Songs. The author of Revelation alludes to the difficult reading in Cant. 1.2 in order to signal that Jesus is to be identified with the lover of the Song of Songs. As such, Rev. 1.13 represents an early attestation of the Christian tradition of allegorical interpretation of the Song of Songs. Evidence is adduced from the pseudepigraphic Testament of Solomon to corroborate the notion that early Christian interpreters were aware of the problem in Cant. 1.2 and regarded it as a distinctive feature of the poem.
Keywords: LXX and Hebrew vocalization; New Testament use of Song of Songs; body imagery; Son of Man; Rev. 1.13; Cant. 1.2